OPERATIVE NOTES: A SIMPLE YET EFFECTIVE TEACHING RESOURCE FOR TRAINING - Jawaid, Masood; Masood, Zubaida; Humayun, Sidra (Pakistan Armed Forces Medical Journal, 2011)
Objective: To find out the opinion of surgical team about teaching of operative notes and whether writing of operative notes is taught during surgical training. Study Design: Cross Sectional Study Place and Duration of study: Civil Hospital, Karachi from July to September 2007. Methods: Convenience sampling was used to include participants. A questionnaire was filled on the spot that included questions about formal teaching and operative notes, either they should be hand written or typed, how operative notes were learned, knowledge about any guideline, counselling about syntax to be avoided in writing, record of swab and instrument count, opinion about possible implications and need of standard national guidelines. Results: A total of 154 surgical residents and consultants filled in the questionnaires. Responding to question about documenting operative notes, 69.5% preferred them to be hand written while 32.5% wanted typed notes. Most of them (81.8%) think that formal operative notes teaching is important. About half (46.1%) of the surgeons learned operative notes from senior trainee, 40.3% by reading other operative notes and 22.1% learned them by doing. Only 4.5% responded that they had some form of formal teaching about writing operative notes. It is important to realize that not a single respondent knew any guidelines about writing operative notes. Majority of the surgeons (87.7%) felt that there is a need of National guidelines about operative notes. Conclusion: There is lack of teaching about how to write standard operative notes during surgical training. Formal teaching in this regard can improve the quality of documentation and offer multiple advantages including improvement of surgical training and patient care.